Cette aveuglante absence de lumière - Brahim El Guabli (Francosphères)
Drawing on Samia Mehrez’s work on the subversive use of French by Maghrebi writers and Pascale Casanova’s theory on literary dissemination, this article examines the politics of literary production in foreign languages and the exposure of human rights abuses in Tahar Ben Jelloun’s Cette aveuglante absence de lumière. While this fictionalized version of Aziz BineBine’s true disappearance experience in the secret prison camp of Tazmamart (1973–1991) portrays the evolution of Salim and his colleagues in Tazmamart’s ‘necroworld’, it also poses questions about the relationship between literary fame, circulation, and audiences of grave violations of human rights in a globalized literary-scape. I argue that because of his international stature, Ben Jelloun could afford to sabotage the official discourses on state violence in the past and put Moroccan prison experience on the global map of literary engagement with human rights violations.